Foreword - Epure, Manuela (Journal of Economic Development, Environment and People, 2017)
We are living in a globalized world, hence the need to reconsider the way in which we are interacting and working bothlocally and internationally. The Fourth Industrial Revolution not onlybrings us new technologies, but requires a new leadership approach. It is about responsive and responsible leadership that could allow us to keep up with the major changes likelyto occur due to new technologies in place.